Comprehensive Literature Review of Preoperative Tranexamic Acid for Treatment of Bleeding, Edema, and Ecchymosis in Patients Undergoing Rhinoplasty - Sylvia, Sylvia; Viona, Viona (International Medical Journal Corp. Ltd, 2024)
Background: The literature on the use of tranexamic acid (TXA) in rhinoplasty highlights its efficacy in managing intraoperative bleeding, postoperative edema, and ecchymosis. The foundational study by (Ping et al., 2019) conducted a systematic review and meta-analysis, establishing that TXA significantly reduces blood loss and enhances surgical field quality, which is critical for successful nasal surgeries. This study laid the groundwork for understanding the role of TXA in improving surgical outcomes, particularly in minimizing postoperative complications such as edema and ecchymosis around the eyelids. Literature Review: The article